Cabo Verde : Technical Assistance Report-Government Finance Statistics and Public Sector Debt Statistics. (IMF Staff Country Reports; Country Report ;, 2021)
A technical assistance (TA) mission on Government Finance Statistics (GFS) and Public Sector Debt Statistics (PSDS) visited the city of Praia, Republic of Cabo Verde, from July 22 to August 2, 2019, with the aim of putting more and better-quality fiscal data -particularly on PSDS - in the hands of public decision makers. The mission was funded by the Data for Decisions (D4D) fund under module 1 on fiscal data including debt.